Representasi Kehidupan Muslim Suriah di Amerika dalam Novel The Girl in the Tangerine Scarf Karya Mohja Kahf - Alzira Devania Zahra; Fenty Sukmawaty; Erik Candra Pertala (Fakultas Sastra Universitas Nahdlatul Wathan Mataram, 2021)
Living in a country where the majority of the population has conflicting beliefs of course has a lot of influence. Starting from lifestyle, culture, education and others. This study examines the development and growth of Syrian Muslims in America, comparing the lifestyle and cultural differences between Syrian and American Muslims. The purpose of this study is to provide information to students who are interested in studying how Muslims live in countries where the majority have different beliefs. The method used in this study is a descriptive method with a comparative type. The approach used in this research is an ethical-objective approach. The results of this study are that there are many lifestyle and cultural differences between Syrian Muslims and Americans, such as how to dress, discriminate, promiscuity, being alone with the opposite sex, non-halal food and the prohibition of using tampons. Hopefully this research can help students provide information about Muslim life in America and its impact.